ANALISIS LAPORAN HARGA POKOK PRODUKSI BARANG PERCETAKAN PADA PT. LIMBERSA ANUGERAH PRIMA PRINTING PALEMBANG - Dewi Oktavia; Harsi Romli; Lukita Tripermata (Universitas Indo Global Mandiri)
The purpose of this study was to analyze the report the calculation of cost of production at PT. LimbersaAnugerah PrimaPrinting Palembang. Data used in this research are secondary data from the report the cost of production in December 2014 at PT. Limbersa Anugerah PrimaPrinting Palembang.The data analysis technique used in this study is a comparative qualitative data analysis techniques, the method of research which compares with the existing theory with the data obtained from the field study.The results showed; (1) The results of the calculation of costs of production by the company showed Rp 1,369, while the results of calculations based on theoretical analysis of Rp 3,452. Thus, the difference between production costs in the calculation of the company with analysis based on the theory that is Rp 2,083 for goods orders printed with blank invitation in December 2014. The result of the calculation according to the company's production cost is Rp 1,019 results show calculations based on theoretical analysis of Rp 3,102. So the difference for goods orders printed invitations without any form of Rp 2,083 / sheet. Difference in cost of production for goods orders calendar size 35x50cm print in December 2014 amounting to Rp 2,083 / sheet. (2) the post-production costs are overhead costs that are not taken into account the company, whereas the post is very important to know because it affects the cost of production. So when there are differences in the calculation results calculated production costs of machinery depreciation expense amounting to Rp 25,000,000, -. Machinery depreciation expense per month is Rp2.083million.